Genomic characterization of highly pathogenic H5 avian influenza viruses from Alaska during 2022 provides evidence for genotype-specific trends of spatiotemporal and interspecies dissemination - Christina A. Ahlstrom; Mia Kim Torchetti; Julianna Lenoch; Kimberlee Beckmen; Megan Boldenow; Evan J. Buck; Bryan Daniels; Krista Dilione; Robert Gerlach; Kristina Lantz; Angela Matz; Rebecca L. Poulson; et al. (Emerging Microbes and Infections)
The ongoing panzootic of highly pathogenic H5 clade 2.3.4.4b avian influenza (HPAI) spread to North America in late 2021, with detections of HPAI viruses in Alaska beginning in April 2022. HPAI viruses have since spread across the state, affecting many species of wild birds as well as domestic poultry and wild mammals. To better understand the dissemination of HPAI viruses spatiotemporally and among hosts in Alaska and adjacent regions, we compared the genomes of 177 confirmed HPAI viruses detected in Alaska during April–December 2022. Results suggest multiple viral introductions into Alaska between November 2021 and August or September 2022, as well as dissemination to areas within and outside of the state. Viral genotypes differed in their spatiotemporal spread, likely influenced by timing of introductions relative to population immunity. We found evidence for dissemination of HPAI viruses between wild bird species, wild birds and domestic poultry, as well as wild birds and wild mammals. Continued monitoring for and genomic characterization of HPAI viruses in Alaska can improve our understanding of the evolution and dispersal of these economically costly and ecologically relevant pathogens.